Intraocular administration of tetramethylpyrazine hydrochloride to rats: a direct delivery pathway for brain targeting? - Dan Mao; Fang Li; Qun Ma; Manman Dai; Huimin Zhang; Luyu Bai; Ning He (Taylor & Francis Group, 2019)
The purpose of this study was to compare the pharmacokinetic profile of tetramethylpyrazine hydrochloride (TMPH) in rat plasma and tissues following intravenous (iv), intragastric (ig) and intraocular (io) administration. After io, ig and iv administration of a single dose at 10 mg/kg, tissue and plasma samples drawn from the femoral artery were collected at timed intervals. The concentration of TMPH in the samples was analyzed using high-performance liquid chromatography (HPLC). The area under the concentration-time curve (AUC) and the drug targeting efficiency percentage (DTE(%)) were calculated to evaluate the targeting efficiency of the drug with the three different administration routes. After io administration, TMPH was rapidly absorbed to reach its peak plasma and brain concentration within 5 min. The systemic bioavailability obtained with io administration was greater than that obtained through the ig route (63.22% vs. 16.88%). The AUCt rank order of the iv administration group was AUCkidney >AUCheart >AUCliver >AUCbrain >AUCspleen >AUClung; that of the ig administration group as AUCkidney >AUCliver >AUCheart >AUCspleen >AUCbrain >AUClung; while that of the io administration group was AUCkidney >AUCbrain >AUCheart >AUCliver >AUCspleen >AUClung. The ratio of the AUCbrain value between the io route and iv injection was 1.05, which was greater than that obtained after ig administration (0.30). The DTE after io administration was calculated: brain (165.72%), heart (97.76%), liver (113.06%), spleen (105.31%), lung (163.40%) and kidney (135.31%). The io administration group showed obvious drug transport to the brain. These results indicate that TMPH is rapidly absorbed from the eye into the systemic circulation, and there may be a direct translocation pathway for TMPH from the eye to the brain. Therefore, io administration of TMPH could be a promising alternative to intravenous and oral approaches.